Catheter ablation of ventricular tachycardia in structurally abnormal hearts: results of an incremental strategy to produce good long-term outcomes. (22nd September 2015) - Thomas, G; Sawhney, V; Ezzat, V; Duncan, E; Watts, T; Appanna, G; Shah, N; Finlay, M; Sporton, SC; Schilling, RJ
Abstract : Introduction: Catheter ablation is an effective method for palliation of ventricular tachycardia (VT) in the setting of structural heart disease, but questions remain about the long-term success. We have applied an incremental strategy for catheter ablation of VT between 2003 and 2008 and examined its long-term outcome. Methods: If patients had stable tolerated VT they underwent map-guided ablation. If an endocardial source could not be identified then an epicardial approach was used. If VT was not tolerated or non-sustained (unmappable) then substrate modification was performed guided by pace mapping if an ECG was available. If substrate was extensive for either mappable or unmappable VT and a suitable coronary vessel was present then ethanol ablation was performed. Patients were followed up in clinic and by telephone interview. Results: 53 patients (male 48) with ischaemic heart disease n = 38 (72%), idiopathic dilated cardiomyopathy n = 11 (20%), valvular heart disease n = 2 (4%) and congenital heart disease n = 2 (4%), with a mean age of 63 years (range 20–82 years) underwent catheter ablation for VT. Ejection fraction was less than 35% in 29 (55%) patients. 46 (87%) patients had implantable cardioverter defibrillators (ICD). Clinical VT was spontaneous in 23 (43%) patients, inducible in the remaining 30 (57%) patients and haemodynamically unstable in 14 (26%) patients. The mean number of inducible clinical VT was 1.2 (range 1–4) and non-clinical VT was 1.6 (range 1–4). Mapping techniques included conventional n = 12 (23%), Carto n = 36 (68%) and non-contact n = 5 (9%). VT origin was left ventricle in 50 (94%) and right ventricle in three (6%) patients. Ablation energy was delivered via an irrigated 4 mm catheter in 40 (75%), a non-irrigated 4 mm catheter in eight (15%), an 8 mm non-irrigated catheter in one (2%) patient; cryo (epicardial only) in two (4%) and ethanol ablation was performed in two (4%) patients. Epicardial ablation was required in eight (15%) patients. A focal ablation strategy was used in 37 (70%), substrate modification in nine (17%) and linear in seven (13%) patients. Post-ablation, clinical VT was non-inducible in 41 (77%) yet persisted but was modified and amenable to anti-tachycardia pacing (ATP) in 12 (23%) patients. There were no procedural deaths. Complications included a transient ischaemic attack (n = 1) and pericardial tamponade requiring drainage (n = 1). Mean follow-up was 27.2 months (range 1.2–65.9 months). Nine (17%) patients died during follow-up. ICD interrogation of the survivors (n = 39) revealed that 36 (92%) remained shock free and 27(69%) remained free from (appropriate) ATP. Conclusions: An incremental strategy of catheter ablation for VT results in excellent long-term outcomes with low complications.